Pertimbangan Hakim dalam Pemidanaan Pelaku Tindak Pidana Pengedaran Mata Uang Palsu - Westi, Adella Putri; Yunanto, Yunanto (Universitas Batanghari Jambi, 2024)
The purpose of this research is first to find out how the criminal responsibility of the perpetrators of the crime of circulating counterfeit currency is? and secondly, what are the judges' legal considerations in deciding cases of criminal acts of circulating counterfeit currency? In order to answer these problems, normative juridical and empirical juridical approaches are used. Data collection was carried out by means of literature and field studies, then the data were analyzed qualitatively. Based on the results of the research and discussion it was concluded that the defendant's form of criminal responsibility against the defendant Hendi Setio who was proven to have committed the crime of counterfeiting currency was imprisonment for 2 years and 6 months and a fine of IDR 100,000,000. In deciding the case the judge has considered the juridical, sociological, and philosophical aspects. Based on these conclusions, it is hoped and suggested that socialization or counseling be carried out on the characteristics of genuine rupiah currency to the public so that it is hoped that the circulation of counterfeit money will decrease. In addition, the judge in imposing a sentence must always pay attention to the purpose of punishment by fulfilling a sense of justice for both the convict, the victim and the wider community.